2020
DOI: 10.1108/f-04-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of campus wayfinding signage: a comparative study from Hong Kong and Pakistan

Abstract: Purpose Complex environments have a paucity of visual wayfinding information creating a strenuous situation for the new visitors. University campuses situated in the central urban areas with multi-storey structures and complex spatial layouts have poor environmental legibility. International students and visitors with diverse cultural backgrounds feel disoriented during wayfinding in these environments. The purpose of this paper is to investigate the cultural and individual differences affecting wayfinding beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
13
0
2
Order By: Relevance
“…Being exploratory, this study demonstrated a substantial amount of differences related to the cultural influences and individual diversities in the preference of university signage design. Multiple studies (Troncoso, 2014;Ahmed, 2015;Iftikhar et al, 2020a) explored the cultural influences on human wayfinding behaviour to facilitate institutional settings. For this study, the aim was to investigate the cultural influences on user preferences by comparing participants from Hong Kong and Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Being exploratory, this study demonstrated a substantial amount of differences related to the cultural influences and individual diversities in the preference of university signage design. Multiple studies (Troncoso, 2014;Ahmed, 2015;Iftikhar et al, 2020a) explored the cultural influences on human wayfinding behaviour to facilitate institutional settings. For this study, the aim was to investigate the cultural influences on user preferences by comparing participants from Hong Kong and Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…The wayfinding systems consisting of static and digital information need to be synthesised for mitigating the contemporary wayfinding issues (Jeffrey, 2017). The complex university environments require a robust design for the effective delivery of environmental information because of the inefficacy of the current wayfinding system (Iftikhar et al, 2020a). Therefore, it is necessary to investigate the current practices of users' behaviour and preferences regarding information syntheses.…”
Section: Wayfinding Information Systemsmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Iftikhar,hH. Salman Asgharaand Yan Luximon, (2020) [12] berjudul "The efficacy of campus wayfinding signage: accomparativecstudy from HongnKong and Pakistan". Penelitian ini bertujuanpuntuk menyelidiki perbedaan budaya dan individuallyang mempengaruhi perilaku wayfinding.…”
Section: Metode Penelitianunclassified